2023
DOI: 10.3389/fmicb.2023.1124672
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and bioactivity of small-molecule antimicrobial peptides from Protaetia brevitarsis Lewis larvae

Abstract: Antimicrobial peptides (AMPs) are widely recognized as promising natural antimicrobial agents. Insects, as the group of animals with the largest population, have great potential as a source of AMPs. Thus, it is worthwhile to investigate potential novel AMPs from Protaetia brevitarsis Lewis larvae, which is a saprophagous pest prevalent in China. In this study, comparing the whole-genome sequence of Protaetia brevitarsis Lewis larvae with the Antimicrobial Peptide Database (APD3) led to the identification of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Currently, five different membrane-target models are considered to explain the mode of action of AMPs on biological membranes [ 64 , 65 ]: (i) the Barrel-stave model, in which the peptide monomers associate and form a bundle of helices embedded in the membrane, forming a transmembrane channel [ 66 ]; (ii) the toroidal pore model (also called wormhole), in which the amphipathic peptide interacts electrostatically with the phospholipid–plasma membrane in a perpendicular orientation relative to the membrane bilayer. In this way, the peptide exerts pressure on the membrane and separates the polar heads elements of phospholipids, resulting in the upper lipid monolayer curving bend through the pore in such a way that the pore lumen consists of peptide molecules and polar heads of phospholipids mixed together [ 66 ]; (iii) the carpet-like model, in which the AMP accumulates on the surface of the plasmatic membrane due to the electrostatic interaction between the positively charged peptide residues and the negative charges of phospholipids, covering it similarly to a carpet, which lead to membrane permeabilisation [ 65 , 66 ]; (iv) the aggregate channel model, which assumes that a supramolecular peptide–lipid complex is formed that mediates the mutually coupled trans-bilayer transport of lipid and peptides, implicitly assuming that informal aqueous channels exist within these aggregates, allowing the free passage of ions and possibly larger molecules [ 64 , 67 ]; and (v) the detergent-like model, in which AMPs aggregates in the membrane surface and after reach a critical concentration promote a micellisation process in the phospholipid bilayer [ 65 ]. Molecular dynamics simulations showed that jelleine-I acts by increasing the pressure on the lipid bilayer of the bacterial membrane [ 50 ].…”
Section: Pharmacological Proprietiesmentioning
confidence: 99%
“…Currently, five different membrane-target models are considered to explain the mode of action of AMPs on biological membranes [ 64 , 65 ]: (i) the Barrel-stave model, in which the peptide monomers associate and form a bundle of helices embedded in the membrane, forming a transmembrane channel [ 66 ]; (ii) the toroidal pore model (also called wormhole), in which the amphipathic peptide interacts electrostatically with the phospholipid–plasma membrane in a perpendicular orientation relative to the membrane bilayer. In this way, the peptide exerts pressure on the membrane and separates the polar heads elements of phospholipids, resulting in the upper lipid monolayer curving bend through the pore in such a way that the pore lumen consists of peptide molecules and polar heads of phospholipids mixed together [ 66 ]; (iii) the carpet-like model, in which the AMP accumulates on the surface of the plasmatic membrane due to the electrostatic interaction between the positively charged peptide residues and the negative charges of phospholipids, covering it similarly to a carpet, which lead to membrane permeabilisation [ 65 , 66 ]; (iv) the aggregate channel model, which assumes that a supramolecular peptide–lipid complex is formed that mediates the mutually coupled trans-bilayer transport of lipid and peptides, implicitly assuming that informal aqueous channels exist within these aggregates, allowing the free passage of ions and possibly larger molecules [ 64 , 67 ]; and (v) the detergent-like model, in which AMPs aggregates in the membrane surface and after reach a critical concentration promote a micellisation process in the phospholipid bilayer [ 65 ]. Molecular dynamics simulations showed that jelleine-I acts by increasing the pressure on the lipid bilayer of the bacterial membrane [ 50 ].…”
Section: Pharmacological Proprietiesmentioning
confidence: 99%
“…The importance of helical structure allows AMPs to be continuously exploited for potential individual use or in combination with established antibiotics, especially in the new era of treating multidrug resistant bacteria affecting both human and animal health ( Lei et al, 2019 ; Fu et al, 2023 ). Highlighting their advantages, AMPs offer a slower emergence of resistance, rapid lethal action, and effective control of biofilms, positioning them as optimal candidates for treatment of drug-resistant pathogens ( Magana et al, 2020 ).…”
Section: Improving the Structure Of Amps To Enhance Their Activitymentioning
confidence: 99%
“…The most abundant fatty acid, oleic acid, accounts for more than 58% of the total fatty acids [ 9 , 11 ]. Although nutritional and functional chemical composition can be changed in response to feed materials and supplementary feeds [ 6 , 10 , 11 ], P. brevitarsis larvae also have a broad range of pharmacological activities, including anti-obesity and anti-diabetic effects [ 12 , 13 ], therapeutic effects on prostatic hyperplasia [ 14 ], the inhibition of osteoclastogenesis [ 15 ], neuroprotective effects against seizures and neurodegeneration [ 16 ], anti-bacterial and anti-inflammatory activities [ 17 , 18 ], and an anti-thrombotic function [ 19 ].…”
Section: Introductionmentioning
confidence: 99%